2013
DOI: 10.1038/nm.3350
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune correlates of protection against symptomatic pandemic influenza

Abstract: The role of T cells in mediating heterosubtypic protection against natural influenza illness in humans is uncertain. The 2009 H1N1 pandemic (pH1N1) provided a unique natural experiment to determine whether crossreactive cellular immunity limits symptomatic illness in antibody-naive individuals. We followed 342 healthy adults through the UK pandemic waves and correlated the responses of pre-existing T cells to the pH1N1 virus and conserved core protein epitopes with clinical outcomes after incident pH1N1 infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
760
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 794 publications
(810 citation statements)
references
References 54 publications
41
760
3
6
Order By: Relevance
“…These data, highlight and confirm that T cells confer a degree of protection against the clinical symptoms of influenza A virus infection. Most commercially available influenza vaccines primarily induce strain-specific antibodies, however it has been demonstrated that heterosubtypic T cells can confer broad-spectrum protection (32)(33)(34). A correlation between IAV-directed T cells and reduced viral shedding with less severe illness in humans has been demonstrated in a number of clinical studies (32,33,35).…”
Section: Prime-boost Vaccinated Mice Intranasally Challenged With DIVmentioning
confidence: 99%
See 1 more Smart Citation
“…These data, highlight and confirm that T cells confer a degree of protection against the clinical symptoms of influenza A virus infection. Most commercially available influenza vaccines primarily induce strain-specific antibodies, however it has been demonstrated that heterosubtypic T cells can confer broad-spectrum protection (32)(33)(34). A correlation between IAV-directed T cells and reduced viral shedding with less severe illness in humans has been demonstrated in a number of clinical studies (32,33,35).…”
Section: Prime-boost Vaccinated Mice Intranasally Challenged With DIVmentioning
confidence: 99%
“…Most commercially available influenza vaccines primarily induce strain-specific antibodies, however it has been demonstrated that heterosubtypic T cells can confer broad-spectrum protection (32)(33)(34). A correlation between IAV-directed T cells and reduced viral shedding with less severe illness in humans has been demonstrated in a number of clinical studies (32,33,35). It has also been demonstrated that protective levels of NP-specific T cell responses are found in 43% of the adult population (36).…”
Section: Prime-boost Vaccinated Mice Intranasally Challenged With DIVmentioning
confidence: 99%
“…This cross-reactive immunity may be what protects many adults from severe illness during a pandemic. 43 Between 2008 and 2014, uptake of LAIV in US 2-8 year olds increased from 20.1% to 38%. 44 One suggestion is that VE observations in the US are a result of recurrent exposure to LAIV over a prolonged time.…”
Section: (Ii)prior Vaccination and Immunitymentioning
confidence: 99%
“…8,9 As far as T lymphocyte responses are concerned, several studies have shown that human CD4 C and CD8 C T cell responses typically cross-react to multiple influenza strains and subtypes, and mainly target internal components of the virus, [10][11][12] and that both CD4 C and CD8 C T cells may independently protect humans from infection or disease. 13,14 Evidence from elderly subjects, in whom the antibody response is quantitatively poor compared to adults, 15 suggests that CD4 C and CD8 C T cell responses may correlate better with protection. [16][17][18] Studies focusing on identifying early predictors of correlates of protection following infection or vaccination have identified an array of other molecular signatures.…”
Section: Introductionmentioning
confidence: 99%